2021
DOI: 10.1002/advs.202003046
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution In‐Situ Synchrotron X‐Ray Studies of Inorganic Perovskite CsPbBr3: New Symmetry Assignments and Structural Phase Transitions

Abstract: Perovskite photovoltaic ABX 3 systems are being studied due to their high energy-conversion efficiencies with current emphasis placed on pure inorganic systems. In this work, synchrotron single-crystal diffraction measurements combined with second harmonic generation measurements reveal the absence of inversion symmetry below room temperature in CsPbBr 3 . Local structural analysis by pair distribution function and X-ray absorption fine structure methods are performed to ascertain the local ordering, atomic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
4
4
0
1
Order By: Relevance
“…58 They revealed that a first-order transition from the cubic phase to tetragonal phase at 403 K, and a second-order change from the tetragonal phase to orthorhombic phase at 361 K. Recently, Liu et al investigated structural phase transitions of CsPbBr 3 using a high-resolution in-situ synchrotron XRD method. 59 They observed a bulk structure with a space group of cubic Im 3̄ above 410 K, which was extremely similar to a previously reported Pm 3̄ m unit cell. The cubic CsPbBr 3 then underwent a transition to monoclinic P 2 1 / m between 300 K and 410 K, and to the monoclinic polar group Pm below 310 K. After confirmation, it was found that the β angle in monoclinic cells was close to 90°, which could be roughly considered the orthorhombic phase.…”
Section: Resultssupporting
confidence: 85%
“…58 They revealed that a first-order transition from the cubic phase to tetragonal phase at 403 K, and a second-order change from the tetragonal phase to orthorhombic phase at 361 K. Recently, Liu et al investigated structural phase transitions of CsPbBr 3 using a high-resolution in-situ synchrotron XRD method. 59 They observed a bulk structure with a space group of cubic Im 3̄ above 410 K, which was extremely similar to a previously reported Pm 3̄ m unit cell. The cubic CsPbBr 3 then underwent a transition to monoclinic P 2 1 / m between 300 K and 410 K, and to the monoclinic polar group Pm below 310 K. After confirmation, it was found that the β angle in monoclinic cells was close to 90°, which could be roughly considered the orthorhombic phase.…”
Section: Resultssupporting
confidence: 85%
“…Phase transitions can be monitored spectroscopically by emission and absorption at the vibrational, rotational, and phonon spectral range from volumes comparable to the wavelength of light 20,21 as well as by diffraction of synchrotron Xrays or free-electron lasers (X-FELs). [22][23][24] Here, we validate the hypothesis of polarisation analysis using non-propagating evanescent light. Anisotropy of absorbance is determined by measuring the difference between two perpendicular s-and p-polarisation components, in amplitude and phase, from the fit of the angular dependence of transmittance through an ATR setup.…”
Section: Nanoscale Horizonssupporting
confidence: 61%
“…Phase transitions can be monitored spectroscopically by emission and absorption at the vibrational, rotational, and phonon spectral range from volumes comparable to the wavelength of light 20,21 as well as by diffraction of synchrotron X-rays or free-electron lasers (X-FELs). 22–24…”
Section: Introduction: Polarisation As An Analytical Toolmentioning
confidence: 99%
“…As the temperature increases further, the shift of the bands slows down, which is associated with phase transitions in the CsPbBr 3 perovskite [36]. Simultaneously with the shift, the PL bands are broadened, probably due temperature range T = 10−170 K. The linear dependence is typical for the interaction with acoustic phonons.…”
Section: Photoluminescence Upon Non-resonant Excitationmentioning
confidence: 96%